2018
DOI: 10.1016/j.tsf.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and tribological behavior of Ti/TiN and TiAl/TiAlN coated austempered ductile iron

Abstract: Bilayer Ti/TiN and TiAl/TiAlN coatings were deposited onto austempered ductile iron (ADI) substrates by cathodic arc deposition in an industrial device. Structure and mechanical properties of the coated samples were comparatively examined. Wear behavior of the coated samples was investigated in comparison with uncoated ADI by means of rolling contact fatigue (RCF) tests, performed in a flat washer type testing rig and using lubricated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Table 1 summarizes the results obtained using this technique. Accordingly, the aluminium fraction in the TiAlN coating is approximately 0.54, from which a cubic face centred NaCl lattice structure can be predicted [42,44]. Besides, the CrAlN chemical composition exhibits a higher aluminium fraction, 0.75.…”
Section: Resultsmentioning
confidence: 96%
“…Table 1 summarizes the results obtained using this technique. Accordingly, the aluminium fraction in the TiAlN coating is approximately 0.54, from which a cubic face centred NaCl lattice structure can be predicted [42,44]. Besides, the CrAlN chemical composition exhibits a higher aluminium fraction, 0.75.…”
Section: Resultsmentioning
confidence: 96%
“…Finally, if the performance of the coatings deposited using the industrial device is compared, it can be seen that the critical loads of the TiAl/TiAlN are lower. According to previous studies [44,45], this behavior can be ascribed to a higher elastic modulus of the TiAl/TiAlN coating with respect to Ti/TiN, since a greater elastic modulus mismatch between substrate and coating increases the probability of coatings to suffer cracking and/or delamination under the effects of the plastic strain accumulated in ADI substrates during tests.…”
Section: Mechanical Behaviormentioning
confidence: 83%
“…However, the performance of Ti 1- x Al x N coatings depends strongly on their crystal structure which changes from cubic to hexagonal at an Al content x = 0.6 and causes a decrease in hardness and wear resistance [2730]. The authors of the present work compared the wear behaviour, under lubricated rolling contact conditions, of ADI coated with TiN and TiAlN films deposited by CAD and by PBIID [3133]. It was found that, under the deposition conditions used, TiN and TiAlN coatings grew with a cubic-NaCl type structure.…”
Section: Introductionmentioning
confidence: 99%